ON ADOPTION OF SR (SANITARY RULES) 2.6.1.2622-10 "HYGIENIC REQUIREMENTS TO THE RADIATION SAFETY PROVISIONS AT THE GAS CONDENSATE UNDERGROUND STORAGE RESERVOIRS CREATED BY THE NUCLEAR EXPLOSION TECHNOLOGY" - . Роспотребнадзор (Радиационная гигиена)
.